2014
DOI: 10.1109/tuffc.2014.6689784
|View full text |Cite
|
Sign up to set email alerts
|

The study of piezoelectric lateral-electric-field-excited resonator

Abstract: The piezoelectric lateral-electric-field-excited resonator based on an X-cut lithium niobate plate has been investigated. Two rectangular electrodes were applied on one side of the plate so that the lateral electric field components were parallel to the crystallographic Y-axis and excited the longitudinal wave in the gap between the electrodes. The region around the electrodes was covered with a special absorbing varnish to suppress the spurious oscillations. The effect of the absorbing coating width on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…Similar limits for series resonance are 1075-11,638 and 1402-13,038 for the first and the second resonator, respectively. Comparison with the data cited in [10] demonstrates a sufficiently high acoustic decoupling between the resonators. This is also confirmed by measuring parameter S 12 that has exceeded 50 dB in absolute value in all the cases considering.…”
Section: Discussion Of Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Similar limits for series resonance are 1075-11,638 and 1402-13,038 for the first and the second resonator, respectively. Comparison with the data cited in [10] demonstrates a sufficiently high acoustic decoupling between the resonators. This is also confirmed by measuring parameter S 12 that has exceeded 50 dB in absolute value in all the cases considering.…”
Section: Discussion Of Resultssupporting
confidence: 53%
“…This approach has allowed us to form a clear resonance frequency dependence of electric impedance or admittance for electrodes with simple rectangular shape. It has been shown that the Q-factor of the resonator may be changed in very wide limits by varying a gap between the electrodes and the width of covered region of the electrodes [10]. The resonator's characteristics appeared to be independent of lateral dimensions and shape of the plate.…”
Section: Introductionmentioning
confidence: 99%
“…The central problem with the design of resonators is suppression of unwanted oscillations to ensure a high Q-factor for a given resonant frequency. There are several ways to solve the problem, particularly, selection of optimal shape for electrodes and their strict orientation about the crystallographic axes of the plate [6,8,9] or by applying an absorbing layer to a certain part of the resonator [7,10,11]. The potentials of the resonators as liquid sensors have been demonstrated in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…This paper presents a liquid sensor based on the lateral electric field-excited resonator with the simplest geometry of electrodes placed at the X-cut lithium niobate plate and demonstrates its potentials for the conducting and viscous liquids. To suppress the unwanted oscillations an absorbing film was coated on a certain part of the resonator [7,10,11]. The impedance or admittance modulus of the resonator is shown to be a more convenient informative parameter for determination of liquid viscosity and conductivity at a fixed frequency near the resonance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation